Optimization of Bioencapsulation of Bacillus sp. to Increase Resistance to Bacterial Wilt and Growth of Cayenne Pepper - Ajeng Distya Anjani; Yenny Wuryandari; Safira Rizka Lestari (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2025)
Cayenne pepper has a high production demand. The high demand does not match the amount of production produced. One of the factors for decreased production is the presence of bacterial wilt disease caused by Ralstonia solanacearum. Bacterial wilt control can be done with the application of antagonistic bacteria, namely Bacillus sp. Bacillus sp. application requires an optimal formulation to maintain bacterial activity in the soil, one of which is Bacillus sp. encapsulation. This study aims to determine the effectiveness of Bacillus sp. encapsulation as a formulation of biological agent bacteria for the control of bacterial wilt disease and cayenne pepper plant growth. This study used the encapsulating material concentration and dosage factors for application to plants. Encapsulation was made using the extrusion method. The results showed that the concentration of 2% sodium alginate and 1.5% gelatin gave a significant difference in disease intensity of 18.89% and in the growth parameters of cayenne pepper plants were able to reach a height of 30.58 cm and a root length of 17.18 cm. The right concentration and high dose provide the ability to suppress intensity and encourage maximum growth